Cloning and Characterization of Two Toll Receptors (PcToll5 and PcToll6) in Response to White Spot Syndrome Virus in the Red Swamp Crayfish Procambarus clarkii - Huang, Ying; Chen, Yihong; Hui, Kaimin; Ren, Qian (Frontiers in Physiology, 2018)
Toll/Toll-like receptors are widely known as key components in the innate immune response of invertebrates. In this study, we identified two novel Toll receptors (PcToll5 and PcToll6) from red swamp crayfish, Procambarus clarkii. The full-length of PcToll5 is 4247 bp, which encodes a putative protein of 1293 amino acids. The complete cDNA sequence of PcToll6 is 4688 bp, encoding an 1195-amino acids polypeptide. Quantitative RT-PCR analysis showed that both PcToll5 and PcToll6 were constitutively expressed in all detected tissues. The highest expression level of PcToll5 was found in intestine, while PcToll6 was expressed higher in gills. PcToll5 and PcToll6 expressions in the intestine or gills were significantly up-regulated to the highest level from 24 to 48 h during the white spot syndrome virus (WSSV) challenge. RNA interference by siRNA results showed that PcToll5 and PcToll6 might regulate anti-lipopolysaccharide factor (PcALF2 and PcALF3) expressions in vivo. Over-expression of PcToll5 and PcToll6 in Drosophila Schneider 2 (S2) cells could also activate expression of Drosophila Antimicrobial peptides (AMPs), including metchnikowin (Mtk), drosomycin (Drs), and attacin A (Atta), and shrimp Penaeidin-4 (PEN4). These findings suggest that PcToll5 and PcToll6 may contribute to the innate immune defense of P. clarkii against WSSV.